Simulation of the interaction between silica surface and acid or alkaline aqueous media - Kravchenko, A.A.; Demianenko, E.M.; Tsendra, O.M.; Lobanov, V.V.; Grebenyuk, A.G.; Terets, M.I. (Поверхность, 2015)
A quantum chemical analysis has been carried out of the equilibrium structure of hydrated HCl and HBr acid complexes and alkaline metal hydroxides on silica surface by means of density functional theory method with extended basis set 6-31++G(d,p) and exchange-correlation functional B3LYP. Deprotonation constants of silica surface hydroxyl group and of its cationic form have been calculated. Методом функціоналу густини з використанням розширеного базисного набору 6‑31++G(d,p) та обмінно-корреляційного функціоналу B3LYP проведено квантовохімічний аналіз будови гідратованих комплексів кислот HCl і HBr та гідроксидів лужних металів на поверхні кремнезему. Розраховані константи депротонування гідроксильної групи групи поверхні кремнезему і її катіонної форми. Методом функционала плотности с использованием расширенного базисного набора 6‑31++G(d,p) и обменно-корреляцийного функционала B3LYP проведен квантовохимический анализ строения гидратированных комплексов кислот HCl и HBr и гидроксидов щелочных металлов на поверхности кремнезема. Рассчитаны константы депротонирования гидроксильной группы поверхности кремнезема и её катионной формы.